Numerical Approximation of Stochastic Volterra-Fredholm Integral Equation using Walsh Function - Paikaray, Prit Pritam; Beuria, Sanghamitra; Parida, Nigam Chandra (Communications in Mathematics and Applications, 2023)
In this paper, a computational method is developed to find an approximate solution to the stochastic Volterra-Fredholm integral equation using the Walsh function approximation and its operational matrix. Moreover, convergence and error analysis of the method is carried out to strengthen its validity. Furthermore, the method is numerically compared to the block pulse function method and the Haar wavelet method for some non-trivial examples.